Contracts and access to Mexico's natural gas resources: The text is not legible on the ground. Issue 134 (August 2022) - Daniel-Aaron Murphy, Trey; Fry, Matthew; Hilburn, Andrew; García-Chiang, Armando
Highlights: Officials tout possibilities of private contracts to produce gas resources. Mexican stakeholders show disconnect between access and contract rights. Contract signatories use contracts for own ends, not for largescale gas production. Examining contract form and function is a fruitful research agenda for geographers. Abstract: We examine how contracts mediate private industry access to state-owned subterranean resources. Using a case study from one of Mexico's most productive onshore natural gas fields, the Burgos Basin, we link contract literatures in geography and critical legal scholarship to answer the following two questions: Does the contract text correspond to how private companies access state-owned subsurface resources, and what purposes do the contracts serve for the contract signatories beyond resource production? The data suggest that contract winners have, so far, limited their drilling activities on the Burgos Basin. This situation draws attention to a puzzle wherein natural gas reserves are not being produced, but the contracts remain active and important to both the contractors and the government. Putting semi-structured interview data into direct conversation with contract text to answer our research questions, we encourage a deeper engagement with how extractive contracts are used to access state-owned resources. First, we uncover how the contract text is not instructive of how or why a private firm will access the resource or why the state enters the contract. Second, we highlight the ways that the contract fails to actualize resource production using a mechanisms of access approach to guide our analysis. Third, we show that resource contracts facilitate relationships and advance the interests of the contract parties regardless of what the actual text purports to do. We finally describe how state-firm resource contracts offer a fruitful area of exploration for geographers interested in resource production.